Endometrial Carcinomas With Subclonal Loss of Mismatch Repair Proteins: A Clinicopathologic and Genomic Study. (3rd May 2023) - Mendoza, Rachelle P.; Wang, Peng; Schulte, Jefree J.; Tjota, Melissa Y.; Jani, Ina; Martinez, Anna C.; Haridas, Rishikesh; Wanjari, Pankhuri; Steinhardt, George; Brown, Noah; Betz, Bryan L.; Chapel, David B.; et al.
Abstract : Subclonal loss of mismatch repair (MMR) proteins has been described in a small subset of endometrial carcinomas (ECs), but the genomic basis for this phenomenon has received limited attention. Herein, we retrospectively evaluated all ECs with MMR immunohistochemistry (n=285) for subclonal loss, and in those (n=6), performed a detailed clinicopathologic and genomic comparison of the MMR-deficient and MMR-proficient components. Three tumors were FIGO stage IA, and one each stage IB, II, and IIIC2. Patterns of subclonal loss were as follows: (1) 3 FIGO grade 1 endometrioid carcinomas with subclonal MLH1/PMS2, MLH1 promoter hypermethylation, and no MMR gene mutations; (2) POLE -mutated FIGO grade 3 endometrioid carcinoma with subclonal PMS2, and PMS2 and MSH6 mutations limited to the MMR-deficient component; (3) dedifferentiated carcinoma with subclonal MSH2/MSH6, as well as complete loss of MLH1/PMS2, MLH1 promoter hypermethylation, and PMS2 and MSH6 mutations in both components; (4) dedifferentiated carcinoma with subclonal MSH6, and somatic and germline MSH6 mutations in both components, but with a higher allele frequency in MMR-deficient foci. Recurrences occurred in 2 patients, one consisted of the MMR-proficient component from a FIGO 1 endometrioid carcinoma, while the other was from the MSH6 -mutated dedifferentiated endometrioid carcinoma. At the last follow-up (median: 44 mo), 4 patients were alive and disease-free and 2 were alive with disease. In summary, subclonal MMR loss reflects subclonal and often complex genomic and epigenetic alterations, which may have therapeutic implications and therefore must be reported when present. In addition, subclonal loss can occur in both POLE -mutated and Lynch syndrome–associated ECs.